THE EFFECT OF SERVICE REQUIREMENTS, SERVICE PROCEDURES, SERVICE TIME AND SERVICE RATES ON PUBLIC SATISFACTION AT THE ORGANIZATIONAL OFFICE OF THE BATAM CITY REGIONAL SECRETARIAT - Nurhasanah; Sabri; Sumardin (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to determine and analyze the influence of Service Requirements, Service Procedures, Service Time, and Service Rates on Public Satisfaction at the Organizational Section of the Regional Secretariat of Batam City. The research method used is a quantitative method with a survey approach. The population in this study were the community who use services at the Organizational Section of the Regional Secretariat of Batam City, with a sample size of 100 respondents. The data collection technique was carried out through the distribution of questionnaires measured using a Likert scale. Data processing and analysis were carried out using the SPSS program.The results of the study indicate that simultaneously Service Requirements, Service Procedures, Service Time, and Service Rates have a positive and significant effect on Public Satisfaction, as evidenced by the F-count value of 90.847 which is greater than the F-table of 2.47 and a significance value of 0.000 <0.05. Partially, Service Requirements have a significant effect on Public Satisfaction with a t-count value of 9.712> t-table 1.985 and a significance of 0.000 <0.05. Service Procedures also have a significant effect on Public Satisfaction with a t-count value of 16.113> t-table 1.985 and a significance of 0.000 <0.05. Service Time has a significant effect on Public Satisfaction with a t-count value of 6.482> t-table 1.985 and a significance of 0.000 <0.05. Furthermore, Service Rates have the most dominant and significant influence on Public Satisfaction with a t-count value of 17.603 > t-table 1.985 and a significance of 0.000 < 0.05. Thus, it can be concluded that improving service quality in all aspects will have an impact on increasing public satisfaction.